Cervical gland area as an ultrasound marker for prediction of preterm delivery: A cohort study - Vajiheh Marsoosi; Reihaneh Pirjani; Mohamad Asghari Jafarabadi; Mina Mashhadian; Saeedeh Ziaee; Ashraf Moini (Shahid Sadoughi University of Medical Sciences, 2017)
Background: Preterm labor is a major cause of perinatal morbidity and mortality and it might be predicted by assessing the cervical change. Objective: To assess the association between absence of cervical gland area (CGA) and spontaneous preterm labor (SPTL). Materials and Methods: This prospective cohort study was performed on 200 singleton pregnant women with a history of SPTL, second-trimester abortion in the previous pregnancy or lower abdominal pain in current pregnancy. Each patient underwent one transvaginal ultrasound examination between 14-28 wk of gestation. Cervical length was measured and CGA was identified and their relationship with SPTL before 35 and 37 wk gestation was evaluated using STATA software version 10. Results: The mean of cervical length was 36.5 mm (SD=8.4), the shortest measurement was 9 mm, and the longest one was 61 mm. Short cervical length (≤18mm) was significantly associated with SPTL before 35 and 37 wk gestation. Cervical gland area (the hypoechogenic or echogenic area around the cervical canal) was present in 189 (94.5%) patients. Absent of CGA had a significant relationship with SPTL before 35 and 37 wk gestation (p=0.01 and p<0.001, respectively). Cervical length was shorter in women with absent CGA in comparison with subjects with present CGA: 37±10 mm in CGA present group and 23±9 mm in CGA absent group (p<0.001). Conclusion: Our study showed that cervical gland area might be an important predictor of SPTL which should be confirmed with further researches.